Documentary sources on Navarre in the Section of “Fondos Contemporáneos” - Magán Merchán, Carmen (Huarte de San Juan. Geografía e Historia, 2010)
One of the largest sections of the National Historical Archive is that of the Contemporary Funds, as it receives the archives of the contemporary Administration, until saturation of the storerooms prevents new entries. The archivist goes over substantial document content taking aside the documentation related to Navarre: Judicial Administration (Supreme Court and General Cause) and the General State Administration (Ministries of Internal Affairs, Presidency of the Government, Justice, Public Works, Agriculture and the Treasury).